2000
DOI: 10.1159/000028893
|View full text |Cite
|
Sign up to set email alerts
|

Tectal Gliomas: Natural History of an Indolent Lesion in Pediatric Patients

Abstract: The mesencephalic tectal glioma is a distinctive form of brain stem glioma with an unusually benign clinical course. Periaqueductal location, lack of contrast enhancement, and long periods of stability are classic features. The clinical management of these lesions, especially at the time of radiographic enlargement varies widely in the published literature. It is unclear whether these progressive lesions need to be treated. Accordingly, clinical and radiologic features of 7 patients were reviewed, with attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
75
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 20 publications
0
75
0
1
Order By: Relevance
“…Patients treated conservatively had tumor volume comparable to our study patients, which is also more in line with tumor volumes reported by others. 1,3,22 The significance of radiological progression is controversial, as progression without concurrent development of clinical symptoms has been observed in a large number of patients with tectal plate gliomas. 1 In regard to imaging characteristics, our study confirms the findings of others that tectal plate gliomas are frequently isointense on T1-weighted images, hyperintense on T2-weighted images, and have a low rate of contrast enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients treated conservatively had tumor volume comparable to our study patients, which is also more in line with tumor volumes reported by others. 1,3,22 The significance of radiological progression is controversial, as progression without concurrent development of clinical symptoms has been observed in a large number of patients with tectal plate gliomas. 1 In regard to imaging characteristics, our study confirms the findings of others that tectal plate gliomas are frequently isointense on T1-weighted images, hyperintense on T2-weighted images, and have a low rate of contrast enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,22 The significance of radiological progression is controversial, as progression without concurrent development of clinical symptoms has been observed in a large number of patients with tectal plate gliomas. 1 In regard to imaging characteristics, our study confirms the findings of others that tectal plate gliomas are frequently isointense on T1-weighted images, hyperintense on T2-weighted images, and have a low rate of contrast enhancement. 3,4,21 None of these imaging features was predictive of tumor enlargement in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Tectal lesions may be indolent. Therefore, first line treatment consists of CSF diversion with no biopsy or further tumor-specific treatment in most cases [9][10][11]. Dorsally exophytic and focal pontomedullary lesions may be pathologically low grade and are frequently associated with long-term survival [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…3,16) However, some cases with atypical neuroimaging and/or clinical progression and some exceptionally aggressive cases required further treatment, such as surgical resection or radiotherapy. 2,5,[7][8][9][14][15][16][18][19][20] In the present case, we decided to perform radical resection of the enhanced tumor because of the unusual aggressive clinical course with hemorrhage and the possibility of malignant components. The surgical cure was successful without neurological deficits.…”
Section: Discussionmentioning
confidence: 91%
“…The overwhelming majority of tectal tumors are low-grade astrocytomas. [1][2][3]10,12,14,16) Accordingly, tectal tumors are often described as a distinctive subset of brain stem glioma with an unusually benign clinical course, and the diagnosis of`benign tectal glioma' is often based on the neuroimaging appearance and indolent clinical course of the lesion. 2,3,13,14) Here we describe a case of tectal pilocytic astrocytoma with the extremely unusual initial manifestation of intracranial hemorrhage.…”
Section: Introductionmentioning
confidence: 99%